A Rare Adrenal Encounter: Case Report of Myelolipoma with Radiological and Histopathological Correlation - Rutul Amrish Parikh; Parikh, Urvi Ruthvij; Parikh, Aesha Amrish; Thakkar, Twinkle Bhashyantkumar; Bhuva, Bhumi Rameshchandra; Goswami, Hansa (Annals of Pathology and Laboratory Medicine, 2025)
Adrenal myelolipoma is a rare, benign tumour of the adrenal gland, usually asymptomatic, unilateral, non-secreting, and an incidental finding. The reported incidence of this tumour is 0.08 to 0.2% of all primary tumours of the adrenal gland. These tumours are also referred to as incidentalomas, as they are reported as incidental findings during imaging procedures like ultrasonography, computed tomography, and magnetic resonance imaging. It is composed of a variable mixture of mature adipose tissue and trilineage hematopoietic elements. Here, we report a case of a 30-year-old female with an adrenal tumour detected on ultrasonography who underwent surgical resection. The confirmatory diagnosis was made on histopathological examination of the resected specimen.